GAYA KEPEMIMPINAN CAMAT TIKKE RAYA DALAM MENINGKATKAN ETOS KERJA PEGAWAI DI KANTOR KECAMATAN TIKKE RAYA KABUPATEN PASANGKAYU - Muhammad Datsir; Nasir Mangngasing; Ani Susanti (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The aim of this research is to determine the Leadership Style of the Head of Tikke Raya District in Improving the Work Ethic of Employees at the Tikke Raya District Office, Pasangkayu Regency, which is studied based on the work motivation theory model according to Hasibuan (2006). :86). 1). Participative, 2). Delegative, 3). Situational, the type of research used is descriptive qualitative with purposive selection of informants and the number of informants selected was 5 people using data collection techniques, 1). Observation, 2). Interview, 3) Documentation. By analyzing all interview results. Results of Research on the Leadership Style of the Regent of Tikke Raya in Improving the Work Ethic of Employees at the Tikke Raya District Office, Pasangkayu Regency. Based on the results of the discussion using three indicators of the Leadership Style of the Regent of Tikke Raya, Pasangkayu Regency, the author can draw the conclusion that the results of research conducted by the author at the Tikke Raya District Office, Pasangkayu Regency, through direct observation and interviews with five informants, from three dimensions/aspects of leadership style namely Participation, Delegation, Situational. The author concludes that the leadership style of the sub-district head in Tikke Raya District, Pasangkayu Regency, as measured by three indicators, is considered to be working well, namely the indicators/dimensions of Participation, Situational, while the indicators/dimensions of Delegation are not working well.